Analysis of The Effectiveness of Unity-Based Vor Learning at Aviation Polytechnic Makassar - Djunaedi; Wahyudi (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The application of augmented reality (AR) technology in aviation education has become an interesting topic in an effort to improve learning effectiveness. This study aims to analyze the effectiveness of augmented reality-based Very High Frequency Omni Directional Range (VOR) learning at Makassar Aviation Polytechnic. The research method used is a pseudo-experiment with a pre-test post-test control group design. The research subjects consisted of two groups, namely the experimental group using AR-based learning and the control group using conventional methods. Data collection was done through cognitive tests and questionnaires of cadets' perceptions of learning. Data analysis was conducted using t-test to compare cognitive test results between experimental and control groups, as well as descriptive analysis to describe cadets' perceptions of learning. The results showed that augmented reality-based VOR learning is effective in improving cadets' understanding of concepts and skills compared to conventional methods. In addition, cadets' perceptions of AR-based learning were generally positive, indicating a good acceptance of the use of such technology in the context of flight learning. These findings make an important contribution to the development of innovative and effective learning methods in aviation education institutions, and provide direction for further development in the integration of AR technology in education.